Determinants of Marketing Performance in Micro Food and Beverage Enterprises: Mediating Role of Competitive Advantage - Dian Anisa Wulandary; Haris Hermawan; Abadi Sanosra (Journal of Enterprise and Development (JED), 2026)
Purpose: This study investigates the effects of digital marketing, market orientation, and product innovation on marketing performance, with competitive advantage serving as an intervening variable among micro food and beverage enterprises.Method: A quantitative research design was applied through a survey involving 98 owners of micro food and beverage businesses. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess both the direct and indirect relationships among the variables.Result: The findings indicate that digital marketing and product innovation exert a significant positive effect on marketing performance, whereas market orientation does not have a significant direct effect. Product innovation also has a significant positive effect on competitive advantage, while digital marketing and market orientation do not significantly influence competitive advantage. Furthermore, competitive advantage has a significant positive effect on marketing performance and mediates the relationships of digital marketing and product innovation with marketing performance. However, it does not mediate the relationship between market orientation and marketing performance.Practical Implications for Economic Growth and Development: The results underscore the strategic importance of enhancing digital marketing capabilities, promoting continuous product innovation, and developing sustainable competitive advantage to improve the performance of microenterprises. These efforts may contribute to local economic development, employment generation, and the competitiveness of micro, small, and medium enterprises (MSMEs).Originality/Value: This study offers a significant contribution by developing an integrated explanatory model that links digital marketing, market orientation, and product innovation to marketing performance through the mediating role of competitive advantage among micro food and beverage enterprises.